Work life balance and its influence on milenial performance of BUMN plantation - R. Turino Januar Budyanto; Yusniar Lubis; Ahmad Rafiki (Institute of Computer Science (IOCS), 2023)
The purpose of this study was to determine the effect of Work Life Balance on individual performance and Talent Management at PTPN IV, which is a subsidiary of BUMN Plantation with main commodities of CPO and Black Tea. Based on the formulation and the relationship between variables processed using the Partial Lest Square (PLS) Model and Smart PLS 3.0 Program with a total of 408 respondents who are employees with managerial positions. The results of the study show that there is a positive and significant influence between Work Life Balance and individual performance and talent management.